The Association Between 2, 4-Dichlorophenoxyacetic Acid and Erectile Dysfunction - Wang, Wei; Ma, Yucheng; Chen, Jiawei; Peng, Liao; Gao, Xiaoshuai; Lin, Lede; Zhang, Fuxun; Xiong, Yang; Qin, Feng; Yuan, Jiuhong (Frontiers in Public Health, 2022)
Background: 2, 4-dichlorophenoxyacetic acid (2,4-D) is one of the most frequently used herbicides in the world and they have been linked with low testosterone; however, studies regarding its effect on erectile function are limited. The current study aimed to determine the association between the 2,4-D exposure and erectile dysfunction (ED) in men from National Health and Nutrition Examination Survey (NHANES). Methods: We analyzed data for urinary 2,4-D levels from 1,311 men (> 20 years of age) in the NHANES 2001 - 2004. ED was assessed by a single, validated survey question. Multivariable logistic regression analysis utilizing sampling weights was performed to determine the relationship between 2,4-D exposure and ED. Results: Multivariable logistic regression models demonstrated no statistically significant association between 2,4-D exposure and ED after full adjustment [odds ratio (OR) 1.02; 95% confidence interval (CI) 0.77 - 1.36; P = 0.882)]. Men in the 2,4-D quartile 4 groups were not associated with an increased risk of ED (OR 1.13; 95% CI 0.74 - 1.75; P for trend = 0.481). Furthermore, the association between urinary 2,4-D level and ED was not significant in the subgroup analysis stratified by age, BMI, cardiovascular disease, hypertension, diabetes and high cholesterol. Conclusion We demonstrated that there was no association between 2,4-D exposure and ED. Further studies are warranted to corroborate our results.